Ruptured ovarian ectopic pregnancy: a rare and challenging diagnosis - A., Archana; Jaget, Nirmala; Saranya, Sri; Sekar, Sindhujha; R., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian ectopic pregnancy is a rare and serious condition that can result in significant maternal morbidity and mortality. This report details the presentation, diagnosis, and surgical management of a 27-year-old woman with a ruptured ovarian ectopic pregnancy. Due to their nonspecific symptoms, ovarian ectopic pregnancies are often only diagnosed intraoperatively and confirmed through histopathological analysis. Prompt diagnosis and timely treatment are essential to prevent life-threatening complications. Whenever possible, fertility preservation should be prioritized through conservative surgical techniques or medical management for carefully selected patients. This case underscores the critical need for heightened awareness and prompt intervention in managing ovarian ectopic pregnancies.